Plant genetic resources Bhutanese perspective: Proceedings of the first national workshop on plant genetic resources natural resources training Institute, Lobeysa, Bhutan, 8-10 November 1999 - Tse-ring, K.; Tamang, A.M.; Mal, B.; Mathur, P.N.; Dorji, R. (2000)
Copies are available from National Biodiversity Programme Ministry of Agriculture Serbithang, Thimpu, Bhutan